Exclusive breast feeding reduces diarrhoeal episodes among children: results from a cross-sectional study among the mothers of under-five children in Kolkata - Banerjee, Nibedita; Chakraborty, Arup; Lahiri, Arista; Biswas, Kalidas (International Journal Of Community Medicine And Public Health, 2019)
Background: Breast feeding is of utmost importance for optimal child growth. This study aims to determine the knowledge on breast feeding among the mothers of under five children and to find out the association between the proportion of exclusive breast feeding and the incidence of diarrhoeal disease. Methods: An institution based cross sectional descriptive study was conducted among ninety (90) mothers of under five children who attended the immunization clinic of a tertiary care hospital with the help of a pre-designed, pre-tested, semi-structured schedule. Mothers were selected by systematic random sampling and interview done after obtaining written consent. Results: The mean age of the respondent mothers were 25.78 years. Among them 77.8% were staying in the nuclear family with the mean education up to 8th standard, 94.4% of home maker. The mean education of fathers was 9th standard with majority (77.8%) occupied either in service or in other occupation. Average no of children per family was 1.3. Majority of mothers’ younger children (66.7%) were male. Majority (66.7%) mothers had heard the term colostrum and 88.3% knew that colostrum has anti-infective property and nutritionally superior. Sixty (66.67%) mothers had exclusively breast fed their children. Out of not exclusively breastfed children 36.67% experienced diarrhoea. Conclusions: Though majority mothers knew about breastfeeding, yet the proportion not having proper knowledge was high. The statistical analysis showed exclusive breast feeding to be highly protective against developing diarrhoeal episodes. In order to generate better breastfeeding practices, addressing the knowledge gap is needed.